Application of 1D 15N and band‐selective 2D 1H‐15N CLIP‐HSQMBC to detect 35/37Cl isotope effect on nitrogen for unequivocal structure elucidation of the N‐Cl moiety in molecules. (2nd September 2021) - Hwang, Tsang‐Lin; Yang, Ning; Cheng, Guilong; Chen, Ying; Cui, Sheng
Abstract: An impurity, designated MS204, was isolated from a scale‐up production of an intermediate toward the synthesis of an active pharmaceutical ingredient. Structural elucidation of this chloro‐containing impurity was performed based on the analysis of the MS and NMR data. Band‐selective 2D 1 H‐ 15 N CLIP‐HSQMBC experiment was developed to unequivocally identify the ionic N‐Cl moiety in the molecule by discovering the two isotope‐shifted nitrogen peaks as 3 to 1 ratio separated by about 1 Δ 15 N( 37/35 Cl) = 19.6 ppb (1.19 Hz) due to the Cl isotope effect. 1D 15 N and 2D 1 H‐ 15 N CLIP‐HSQMBC experiments were applied to commercially available compounds to further confirm the techniques by detecting the isotope shift of nitrogen peaks for the N‐Cl moiety in molecules. Abstract : Band‐selective 2D 1 H‐ 15 N CLIP‐HSQMBC experiment was developed to identify the ionic N‐Cl moiety in the MS204 impurity by discovering the two isotope‐shifted nitrogen peaks as 3 to 1 ratio separated by about 1 Δ 15 N( 37/35 Cl) = 19.6 ppb (1.19 Hz) due to the Cl isotope effect. 1D 15 N experimental data acquired using a broadband cryoprobe setting with sufficient sample can be applied to elucidate the N‐Cl moiety in molecule by detecting the two isotope‐shifted nitrogen peaks due to the Cl isotope effect.